Acute Retinal Necrosis: A Review of Diagnosis and Management - Pattarat Wetchapit; Usanee Tungsattayathitthan; Sutasinee Boonsopon; Nattaporn Tesavibul; Pitipol Choopong (Siriraj Medical Journal)
Acute retinal necrosis (ARN) is a profound infection of the retina, marked by acute panuveitis, retinal periarteritis, and widespread necrotizing retinitis. The etiology of ARN involves human herpesviruses, such as herpes simplex virus (HSV) and varicella-zoster virus (VZV), which can lead to severe visual impairment or even blindness. A diagnosis of ARN is based on clinical characteristics and disease progression according to the standard diagnostic criteria established by the American Uveitis Society (AUS) in 1994. The polymerase chain reaction (PCR) of aqueous specimens can enable identification of the type of virus. Early initiation of antiviral medication is essential for treatment efficacy to stop lesion progression, accelerate the healing process, and prevent contralateral eye involvement. Ocular complications of ARN include atrophic retina, multiple retinal breaks, rhegmatogenous retinal detachment (RRD), tractional retinal detachment (TRD), optic atrophy, macular edema, epiretinal membrane (ERM), and retinal and optic disc neovascularization. This review summarizes the clinical features, diagnostic criteria, and recently recommended ARN management.